Given that:
James is 6 times older than his friend Zach, if Zach added 8 to his age and multiplied this sum by 3.
Explanation:
Let the Zach's age be Z years.
6 times older than Zach = 6Z
Zach added 8 to his age and multiplied this sum by 3 = 3(Z+8)
Now,
![6Z=3(Z+8)](https://img.qammunity.org/2021/formulas/mathematics/high-school/nzkc14t8pjs5twcv9rhzjyil6weonhlfat.png)
![6Z=3Z+24](https://img.qammunity.org/2021/formulas/mathematics/high-school/ufjwvdcxzp21xhy9c1djemqsa7v2d7hmsu.png)
![6Z-3Z=24](https://img.qammunity.org/2021/formulas/mathematics/high-school/534fdmtfqoms72i1m6oxr7f9u9cncfxo7g.png)
![3Z=24](https://img.qammunity.org/2021/formulas/mathematics/high-school/6jzlp8yxsk7iz0sda0g3erfi1xvddtuqvm.png)
Divide both sides by 3.
![Z=(24)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/xgxg13gta50x7hd4i4p4vled6nh82f78hc.png)
![Z=8](https://img.qammunity.org/2021/formulas/mathematics/high-school/ozgrbrsa76wq7m0gq2jkai9j3ohu6ke233.png)
Therefore, the required equation is
and Zach's age is 8 years.